(untitled) (African Journal of Biomedical Research, 2024)
The inhibition of carbohydrate metabolizing enzymes is an important strategy in the management of postprandial hyperglycemia. The present study evaluated the anti-hyperglycemic effect of sweet potato by assessing its inhibitory effects on some carbohydrate enzymes linked to type 2 diabetes. The influence of the aqueous extract of orange-fleshed sweet potato tubers (OSPT) and hydromethanolic extract of orange-fleshed sweet potato leaves (OSPL) on the activities of α-glucosidase, α-amylase, sucrase and maltase were assessed using established techniques. The results showed that OSPL had higher polyphenolic content than OSPT. Both extracts showed significantly lesser inhibition and higher IC50 values on the activities of all the enzymes when compared with acarbose. OSPT had the highest IC50 values, 35.03 ± 1.86, 38.38 ± 2.34, 51.54 ± 2.76, and 70.93 ± 1.98 mg/ml, for α-glucosidase, α-amylase, sucrase and maltase, respectively. However, OSPL showed an appreciable inhibition of all the enzymes and a significantly lower IC50, 5.31 ± 0.92, 5.4 ± 1.82, 4.14 ± 2.86, and 5.46 ± 3.01 mg/ml, for α-glucosidase, α-amylase, sucrase and maltase respectively. These findings indicated that the hydromethanolic extract of the leaves of orange-fleshed sweet potato could serve as a potential antidiabetic agent owing to its ability to effectively inhibit carbohydrate metabolizing enzymes but milder than acarbose